The Effect of Self-Efficacy and Perceived Organizational Support on Performance through Readiness for Change as an Intervening Variable in Employees Working at PT Kenza Hospitality Investment - Baiq Uswatun Hasanah; Sulaimiah (LP2M IAIN Palopo, 2026)
Tourism in Indonesia has experienced significant growth, but along with its expansion, the sector faces challenges related to the readiness of competent human resources (HR). This study aims to analyze the effect of self-efficacy and perceived organizational support on employee performance, with readiness for change as an intervening variable. Using an associative quantitative approach, data were collected through questionnaires distributed to employees of PT Kenza Hospitality Investment in Mandalika, Lombok. The results show that self-efficacy and perceived organizational support positively influence employee performance, both directly and through readiness for change as a mediator. The higher the self-confidence and organizational support, the better the employee performance, and readiness to change also improves their performance. These findings provide implications for companies to enhance employees' self-efficacy and strengthen organizational support to improve performance in the face of change.